2011
DOI: 10.2135/cropsci2011.01.0013
|View full text |Cite
|
Sign up to set email alerts
|

Bermudagrass Cultivar Responses to Sting Nematodes

Abstract: Sting nematodes (Belonolaimus longicaudatus Rau) are the most damaging nematode species on bermudagrass {Cynodon spp.) in Florida. The recent cancellation of the nematicide fenamiphos has resulted in the need for alternative nematode management tactics. Utilization of resistant or tolerant cultivars could be one of the most environmentally friendly and least costly practices for nematode management on turf. However, information about the responses of newer bermudagrass cultivars to sting nematodes is not avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…The tolerant line (AB39) had both low levels of root biomass loss and low nematode populations. These results are line with previous observation from accession screens 23,24 . www.nature.com/scientificreports www.nature.com/scientificreports/ Host metabolome modification by sting nematodes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The tolerant line (AB39) had both low levels of root biomass loss and low nematode populations. These results are line with previous observation from accession screens 23,24 . www.nature.com/scientificreports www.nature.com/scientificreports/ Host metabolome modification by sting nematodes.…”
Section: Discussionsupporting
confidence: 93%
“…To investigate whether sting nematodes modify metabolite production in their host plants, mixed age Belonolaimus longicaudatus nematodes were introduced to the root zones of three African bermudagrass (Cynodon transvaalensis) lines of differing tolerance: one susceptible line (AB03), one moderately tolerant line (AB33), and one tolerant line (AB39). Tolerance in these bermudagrass lines had been determined in previous work; lines are considered tolerant if there was no reduction in root length or had greater root length than the 'Tifway' cultivar despite B. longicaudatus infection 23,24 . In our work, comparison control plants received no nematodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no bermudagrass cultivars with documented resistance against plant‐parasitic nematodes. ‘Tifway’, ‘Celebration’, ‘Princess 77’, and ‘TifSport’ are some cultivars that have been reported as tolerant toward sting nematode (Giblin‐Davis et al, 1992; Pang et al, 2011a, 2011b). Tifway bermudagrass is the most commonly used bermudagrass on golf courses, athletic fields, and lawns in the United States.…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Tifway bermudagrass is the most commonly used bermudagrass on golf courses, athletic fields, and lawns in the United States. Tifway was reported as tolerant toward sting nematode among genotypes available in the late 1980s (Giblin‐Davis et al, 1992), but was found to be less tolerant than many genotypes available two decades later (Pang et al, 2011a, 2011b).…”
Section: Useful Conversionsmentioning
confidence: 99%